ANALISIS PENGARUH PROSES BISNIS INTERNAL TERHADAP KINERJA KEUANGAN RUMAH SAKIT UMUM SWASTA DI KOTA MEDAN - Roswitha Bukit; Azhar Maksum; Sri Mulyani (Jurnal Telaah dan Riset Akuntansi, 2014)
ABSTRACT The objective of the research was to analyze the influence of innovation process, operational process, and post-service process as the indicators of internal business on the financial performance of private general hospitals in Medan. The research used descriptive analytic quantitative method. The population was private general hospitals in Medan. It also used census method since it used all 40 private general hospitals in Medan, and all of them were used as the samples (total sampling). The data were processed by using multiple linear regression analysis. The result of the research showed that the variables of innovation process, operational process, and post-service process simultaneously had positive and significant influence on financial performance of private general hospitals in Medan. Partially, innovation process, operational process, and post-service process had positive and significant influence on financial performance. The ability to predict of the three variables on financial performance was 63.9%, while the rest (36.1%) was influenced by other factors excluded from the research model. Keywords: Financial Performance, Innovation Process, Operational Process, Post-Service Process